Giving and Costless Retaliation in the Power-to-Take Game - Michalis Drouvelis; Nobuyuki Hanaki; Natsumi Shimada; Yuta Shimodaira (Center for Economic Studies and ifo Institute (CESifo), 2023)
Extending the power-to-take game, we explore the impact of two forces that may shape retaliation. In our 2x2 design, i) in addition to taking, the proposers can give part of their endowment to the responders, and ii) in addition to destroying their own endowment in retaliation, the responders can destroy the proposer's endowment. Although these added options lead the responders to retaliate more severely, they do not significantly influence the proposers' behavior. It is only when the proposers can give, and the responders can concurrently destroy the endowment of the proposers that the proposers take significantly less from the responders.
Keywords: A12; C72; C91; 330; power-to-take; giving; emotions; retaliation; experiment